Analysis of Risk Factors of Gastric Low-Grade Intraepithelial Neoplasia in Asymptomatic Subjects Undergoing Physical Examination. (3rd March 2020) - Liu, Yingling; Cai, Yuli; Chen, Si; Gou, Yawen; Wang, Qiaomin; Zhang, Mingli; Wang, Yetao; Hong, Haiou; Zhang, Kaiguang
Abstract : Secondary prevention is an important strategy in gastric cancer. Low-grade intraepithelial neoplasia (LGIN) is the last stage of precancerous lesion, and its timely diagnosis can greatly improve the detection rate of early gastric cancer. We performed a prospective study to analyze the risk factors of gastric LGIN in asymptomatic subjects undergoing physical examination. A total of 3437 subjects were included in this study, and 2259 asymptomatic subjects were investigated from March 2015 to April 2018. Risk factors were evaluated, and the endoscopic features of LGIN and prognosis were described. The overall incidence of LGIN was 19.73% (678/3437), while the incidence of LGIN in the asymptomatic and symptomatic groups was 19.65% (444/2259) and 19.86% (234/1178), respectively (P = 0.884 ). The rate of Helicobacter pylori infection in this physical examination population was 39.13% (35.8% asymptomatic group, 45.5% symptomatic group; P ≤ 0.001 ). Risk factors including age, H. pylori infection, history of antibiotic misuse, and spicy and high-fat diet (all P < 0.05 ) were further verified by multivariate analysis as independent risk factors. History of antibiotic misuse and H. pylori infection showed significant associations with LGIN (odds ratio OR = 6.767, 95% confidence interval (CI) 3.873-11.825 and OR = 3.803, 95% CI 3.009-4.808, respectively). The most common endoscopic classification of LGIN was erosive gastritis (50.78%), and the major endoscopic appearance was Paris IIa (flat with slight elevation located mostly in the antrum). During the mean follow-up period of 15.02 months, 49.4% of LGIN regressed, 0.61% of LGIN progressed, and 50% of LGIN remained unchanged. History of antibiotic misuse and H. pylori infection were predominant risk factors of LGIN in asymptomatic subjects, and those individuals should consider early screening for gastric cancer.